Workplace-based continuing professional development program for physically active learning: designing a framework and prospective directions - Mandelid, Mathias Brekke; Dyngeland, Espen Søreide; Teslo, Ståle; Lerum, Øystein; Tjomsland, Hege Eikeland; Jenssen, Eirik Sørnes; Eriksen, Pernille Buschmann; Wergeland, Tom Christian; Sandal, Marion Østenstad; Stein, Hege; Schjerven, Hilde; Stokke, Rasmus; et al. (Frontiers in Education, 2024)
In 2018, the Centre for Physical Active Learning (SEFAL) designed a comprehensive one-year workplace-based continuous professional development (CPD) program for in-service teachers in Norway. The CPD program aimed to enhance the pedagogical feasibility of integrating physically active learning (PAL) within all theoretical subjects by advancing teachers' competence. This article provides an overview of the SEFAL CPD program's conceptual framework and design. Although the article does not provide an independent evaluation of the framework, we discuss it based on our continual development during the period from 2018 to 2023, during which 1363 teachers from 77 schools participated. As the framework continues to inform the SEFAL CPD, the article concludes by identifying prospective directions and potential avenues for further refinement and utilisation of this and similar programs.